Evaluation of 2 Purification Methods for Isolation of Human Adipose-Derived Stem Cells Based on Red Blood Cell Lysis With Ammonium Chloride and Hypotonic Sodium Chloride Solution. Issue 1 (January 2017) - Li, Sheng-Hong; Liao, Xuan; Zhou, Tian-En; Xiao, Li-Ling; Chen, Yuan-Wen; Wu, Fan; Wang, Jing-Ru; Cheng, Biao; Song, Jian-Xing; Liu, Hong-Wei
Abstract : Background: The present study was conducted to compare 2 purification methods for isolation of human adipose-derived stromal vascular fraction or stem cells (ADSCs) based on red blood cell (RBC) lysis with 155 mM ammonium chloride (NH4 Cl) and hypotonic sodium chloride (NaCl) solution, and try to develop a safe, convenient, and cost-effective purification method for clinical applications. Methods: Adipose-derived stem cells and RBC were harvested from the fatty and fluid portions of liposuction aspirates, respectively. The suitable concentration of hypotonic NaCl solution on RBC lysis for purification of ADSCs was developed by RBC osmotic fragility test and flow cytometry analysis. The effects of 155 mM NH4 Cl or 0.3% NaCl solution on ADSCs proliferation and RBC lysis efficiency were examined by 3-(4, 5-dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide assay and lysis efficiency test, respectively. In addition, the adipogenic and osteogenic capabilities, phenotype and genetic stability of ADSCs were evaluated by oil red staining, alkaline phosphatase activity measurement, flow cytometry, and karyotype analysis, respectively. Results: Sodium chloride solution in 0.3% concentration effectively removed RBCs and did not influence the survival of ADSCs in the 10-minute incubation time. The lysis efficiency did not differ significantly between 0.3% NaCl and 155 mM NH4 Cl. Moreover, the adipogenic and osteogenic capabilities, surface marker expression and karyotype of the ADSCs were not affected by lysis solutions or by lysis per se. However, the proliferation capacity in the 0.3% NaCl group was superior to that in 155 mM NH4 Cl group. Conclusions: Our data suggest that 0.3% NaCl solution is useful for isolating ADSCs from liposuction aspirate for clinical applications with safety, convenience, and cost-effect.